Hyper-specializing in Saxophone Using Acoustical Insight and Deep Listening Skills - Braasch, Jonas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents a novel method of grafting musical wind instruments by exchanging an instrument's standard mouthpiece with different tone generators. Using the concrete example of the soprano saxophone, it describes how, with six other tone generators, including brass, double reed, and free reed mechanisms, the saxophone can be extended to nearly every wind instrument category in the von Hornbostel and Sachs classification system. The book demonstrates how it is possible to play these instrument variations with high proficiency, and describes the method of hyper-specialization, including acoustical insights, conservatory training methods and the underlying philosophy. The latter is based on the cultural traditions of the different wind instrument prototypes and the Deep Listening philosophy of cultivating internal diversity, and approach that leads to a new level of wind instrument virtuosity that offers great timbral variety combined with the flexibility of a regular acoustic wind instrument. .
Introduction -- Acoustics of the Saxophone -- Extended Techniques for the Saxophone.-Deep Listening -- Grafted Instruments -- The Sonic Circle -- Sound Radiation, Recording, and Environment -- Epilogue -- References -- Index -- About the Author.
Keywords: Acoustical engineering; Music; Acoustics; Engineering Acoustics; Music; Acoustics